2019
DOI: 10.1039/c9cc04581c
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the impacts of dynamic soft-templates innate to switchable ionic liquids on nanoparticulate green rust crystalline structures

Abstract: This experimental and theoretical study investigates how dynamic solvation environments in switchable ionic liquids regulate the composition of nanoparticulate green rust.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Besides, the new catalytic intermediate (π → π*) was found after OER reaction (Figure S12f, Supporting Information), indicating that there is π‐π stacking interaction. [ 62 ] The formation of π → π* could be attributed to the change of local electronic structure by electron‐withdrawing functional groups. [ 63 ] In addition, XRD diffraction (Figure S13, Supporting Information) after anode durability tests showed that no additional crystallization signals were detected, indicating that the M–OOH in the transition state is amorphous.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, the new catalytic intermediate (π → π*) was found after OER reaction (Figure S12f, Supporting Information), indicating that there is π‐π stacking interaction. [ 62 ] The formation of π → π* could be attributed to the change of local electronic structure by electron‐withdrawing functional groups. [ 63 ] In addition, XRD diffraction (Figure S13, Supporting Information) after anode durability tests showed that no additional crystallization signals were detected, indicating that the M–OOH in the transition state is amorphous.…”
Section: Resultsmentioning
confidence: 99%
“…X-ray absorption spectroscopy (XAS) and density function theory (DFT) modelling were used to 4 determine possible products of GR synthesis in another related research effort (Figure S2). [5] Compared to previous results, in situ liquid ToF-SIMS provides valuable three-dimensional (3D) visualization of the chemical compounds formed via different synthesis paths in this effort.…”
Section: Andmentioning
confidence: 99%
“…[12][13][14][15] The results of TEM, Helium Ion Microscopy (HIM), and Mössbauer spectroscopy have been reported in our earlier papers. [4,5] The novel synthesis of nano GRs including nano GR-CO 3 * in the presence of CO 2 and methanol employs SWIL solvents .…”
Section: Andmentioning
confidence: 99%
See 1 more Smart Citation